Evaluación del proceso de obtención de aceite de diferentes variedades de bactris gasipaes,de las zonas costa y amazónica del Ecuador. Quevedo. UTEQ.r - Morán Intriago, Tamara Viviana (2015)
This research aims to evaluate three varieties of Bactris gasipaes in the process of obtaining oil through the implementation of two thermal treatments and using two types of solvents, with the purpose of enticing food use. We applied a randomized complete block design (RCBD) with a factorial arrangement A * B * C with three levels in the Factor (chontilla yellow, and red chontilla Chontaduro), two levels in Factor B (crude and pre-cooked) and C Factor (petroleum ether and ethyl ether di) resulting 12 treatments with 2 replicates giving a total of 24 experimental units. We used 2 kg of chontilla red and 2 kg of chontilla yellow of the coastal zone and 2 Kg Chontaduro amazon; which were distributed in 250 g for each treatment and repetitions. We used the method of solvent extraction by manipulating a Soxhlet extractor. The extractions and the analysis of acidity was conducted in the Laboratory of Food Science of the State Technical University Quevedo. The analysis of lipid profile of the oil obtained it is carried out to each of the treatments and their repetitions using the HPLC method (chromatography) corresponding to the internal method of Laboratory Multianalityca Cia, Ltda., in the city of Quito. The results of the proposed variables were calculated using the statistical package Statgraphics centurion XVI version 1.16.18 for the determination of....